1998
DOI: 10.1080/01904169809365563
|View full text |Cite
|
Sign up to set email alerts
|

Use of spectral radiance for correcting nitrogen deficiencies and estimating soil test variability in an established bermudagrass pasture

Abstract: The use of variable rate technology has become increasingly popular for applying plant nutrient elements. The most widely used method for determining variable fertilizer rates is presently based on soil testing and yield mapping. Three field studies (Bumeyville 1995, Burneyville 1996, and Ardmore 1996 were initiated in established Midland bermudagrass [Cynodon dacrylon (L) Pers.] pastures to determine the relationship between spectral radiance at specific wavelengths with forage nitrogen (N) removal and biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Utilizing a reflectance sensor, Sui et al (1998) correctly classified 91% of cotton plants as nitrogendeficient. Taylor et al (1998) reported 60% fertilizer savings in a variable-rate nitrogen application based on readings of Bermuda grass with a reflectance-based sensor. Keskin et al (2004) used 4 wavelength bands at 550, 680, 770, and 810 nm to predict nitrogen content of golf course turfgrass clippings (R 2 > 0.82).…”
mentioning
confidence: 99%
“…Utilizing a reflectance sensor, Sui et al (1998) correctly classified 91% of cotton plants as nitrogendeficient. Taylor et al (1998) reported 60% fertilizer savings in a variable-rate nitrogen application based on readings of Bermuda grass with a reflectance-based sensor. Keskin et al (2004) used 4 wavelength bands at 550, 680, 770, and 810 nm to predict nitrogen content of golf course turfgrass clippings (R 2 > 0.82).…”
mentioning
confidence: 99%
“…For example, Taylor et al. () used the normalized difference vegetation index (NDVI) calculated from spectral reflectance to adjust N fertilizer application rates in pastures according to spatial or temporal variability. This spatially adjusted fertilization reduced fertilizer inputs by 60%, but provided the same yield as fixed‐rate fertilizer plots.…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing is increasingly being used as a timely and nondestructive tool for mapping the nitrogen nutrition status of plants and to rapidly assess the spatial variability within a field based on the canopy reflectance. For example, Taylor et al (1998) (Botha, Leblon, Zebarth, & Watmough, 2007;Darvishzadeha et al, 2008;Lamb et al, 2002), which are generally well correlated with leaf N concentrations. Sanches et al (2013) used hyperspectral data to infer pasture concentrations of N, phosphorus and potassium for NZ pastures in various dairy, and sheep and beef farms around NZ.…”
mentioning
confidence: 99%
“…Site-specific farm planning has great potential for improving crop production and grazing management at the farm-scale. Spatial variation maps of yield using yield monitors (Doerge, 1999) and nutrient deficiencies using spectral radiance (Taylor et al, 1998) can be developed relatively quickly and easily along with GIS. Brock 1997 Variability is apparent at very small scales (less than 1.5 m) (Taylor et al, 1998;Teutsch et al, 1998).…”
Section: Spatial and Site-specific Patterns Of Speciesmentioning
confidence: 99%
“…Spatial variation maps of yield using yield monitors (Doerge, 1999) and nutrient deficiencies using spectral radiance (Taylor et al, 1998) can be developed relatively quickly and easily along with GIS. Brock 1997 Variability is apparent at very small scales (less than 1.5 m) (Taylor et al, 1998;Teutsch et al, 1998). suggested that it is important to look at plant interactions and variability at multiple scales, patch-scale, between patch-scale, and field-scale.…”
Section: Spatial and Site-specific Patterns Of Speciesmentioning
confidence: 99%